Reuse of solarized strawberry substrate in ornamental production of Tagetes erecta: effect of leaching of chemical parameters and plant growth - Sordo, María Del Huerto; Pernuzzi, Cristian; Puerta, Analia Veronica; Rubio, Esteban Julian; Karlanian, Monica; Mollinedo, Victor (INTA y Sbera, 2026)
Poster